علاقة فعالية الذات بالكفاءة التعليمية - موساوي,شيماء; فرحات, هدى (University of Eloued جامعة الوادي, 2024)
تهدف الدراسة للكشف على العلاقةبين فعاليةالذات والكفاءةالتعليميةلدى اساتذةالتعليم الابتدائي حيث انطلقت الدراسةمن الفرضيةالتالية: توجدعلاقةدالةإحصائيابين فعاليةالذات والكفاءةالتعليمية لدى اساتذةالتعليم الابتدائي،وللتأكد من صحةالفرضيات،اعتمدت هذه الدراسةعلى استخدام أداتين لجمع البيانات هما: مقياس فاعليةالذات،مقياس الكفاءةالتعليمية. كمااعتمدت الدراسةعلى المنهج الوصفي الإرتباطي الذي يتوافق مع موضوع الدراسة،حيث طبقت على عينةاستطلاعيةمكونةمن (100) معلم ومعلمة من التعليم الابتدائ يتم اختيارهم بطريقةعشوائية. اعتمدت هذه الدراسةعلى أساليب إحصائية مناسبةوالمتمثلة في: الحزمةالإحصائيةللعلوم الاجتماعيةSPSSالمتمثلةفي الاحصاءالوصفي والاحصاءالاستدلالي وكانت النتائج الدراسة كمايلي: - لاتوجدعلاقةارتباطيةدالةاحصائيابين الكفاءةالتعليميةوفعاليةالذات. - لاتوجدفروق دالةاحصائيابين الذكوروالاناث من اساتذةالتعليم الابتدائي على مقياس الكفاءةالتعليمية. - لاتوجدفروق دالةاحصائيابين الذكوروالاناث من اساتذةالتعليم الابتدائي على مقياس فاعليةالذات. - لاتوجدفروق دالةاحصائيابين فئات الخبرةالمهنيةلدى اساتذةالتعليم الابتدائي على مقياس الكفاءةالتعليمية. - لاتوجدفروق دالةاحصائيابين فئات الخبرةالمهنيةلدى اساتذةالتعليم الابتدائي على مقياس فاعليةالذات.The studyaims to reveal the relationshipbetween self-efficacy and educationalcompetenceamongprimaryeducationteachers. The studystartedfrom the followinghypothesis: There is a statisticallysignificantrelationshipbetween self-efficacy and educationalcompetenceamongprimaryeducationteachers. Partial hypothesesfallunderthishypothesis. To ensure the validity of the hypotheses،thisstudywasadopted. To use twotools to collect data: the self-efficacyscale and the educationalefficiencyscale. - The studyalsorelied on the descriptive،correlationalapproach،whichis compatible with the subject of the study،as itwasapplied to a surveysampleconsisting of (100) male and femaleprimaryeducationteacherswhowerechosenrandomly. - This studyrelied on appropriatestatisticalmethods،namely: the Statistical Package for the Social Sciences (SPSS) ،whichconsists of descriptive statistics and inferentialstatistics. The results of the studywere as follows: - There is no statisticallysignificantcorrelationbetweeneducationalcompetence and self-efficacy. - There are no statisticallysignificantdifferencesbetween male and femaleprimaryeducationteachers on the educationalcompetencyscale. - There are no statisticallysignificantdifferencesbetween male and femaleprimaryeducationteachers on the self-efficacyscale. - There are no statisticallysignificantdifferencesbetween the categories of professionalexperienceamongprimaryeducationteachers on the educationalcompetencyscale - There are no statisticallysignificantdifferencesbetween the categories of professionalexperienceamongprimaryeducationteachers on the self-efficacyscale.
أساتذة التعليم الابتدائي
Keywords: الكفاءةالتعليمة; فاعليةالذات; الخبرةمهنية; efficiency.Self; efficacy; Professional experience